Variation in macular thickness in healthy eyes with or without myopia using optical coherent tomography - Abdulsamad, Sami Jalal; Alwan, Eman H.; ——–, Ahmad Kareem; ——, Ahmad Ismail (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Difference in macular thickness is affected by age, gender and axial length in any ethnic group. The aim of this study is to report normal macular thickness measurement in healthy Iraqi eyes using Optical Coherence Tomography mapping software. Methods: In this cross–sectional study, the macula of 150 eyes (75 healthy subjects) underwent a complete ophthalmic examination including Optical Coherence Tomography. Optical Coherence Tomography parameters of macular thickness were analyzed with baseline variables including age, gender and axial length. Results: Mean central foveal thickness were 217µm and mean macular thickness in 6mm diameter were 245µm. Macular thickness measurement were thinnest at the center of the fovea, thickest within 3mm diameter of the center, and diminish toward the periphery of the macula. The temporal quadrant was thinner than the nasal quadrant. No correlation was found between macular thickness and age. The difference between male and female was significant (P < 0.05). The macula thickness was significantly less in eyes with axial length more than 24mm and more in eyes with axial length less or equal to 24mm (P < 0.05). Conclusion: The macular thickness has a significant correlation with gender and axial length. This normal baseline data of macular thickness of the eyes of Iraqis living in Erbil may be a useful guideline for further research and management of glaucoma and macular diseases.